From Justice To Jazz: Exploring The Improvisational Flow Of Support And Citizenship Behaviour In The Hospitality Industry - Tenri Sayu Puspitaningsih Dipoatmodjo; Zainal Ruma; Rezky Amalia Hamka; Andi Dewi Angreyani; Hery Maulana Arif (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the effect of Procedural Justice on Organizational Citizenship Behaviour (OCB) through Perceived Organizational Support (POS) among hotel employees in Makassar City. The research is motivated by the declining extra-role behaviors of employees, which affect service quality, allegedly driven by perceived procedural injustice and low organizational support. Using a quantitative approach and Partial Least Squares Structural Equation Modeling (PLS-SEM), data were collected through questionnaires from employees of three- to five-star hotels. The results reveal that Procedural Justice has a positive and significant effect on both POS and OCB, directly and indirectly. Moreover, POS functions as both a mediator and a moderator, strengthening the relationship between procedural justice and OCB. The R² and Q² values indicate a high explanatory and predictive relevance, while the Goodness of Fit Index confirms the empirical adequacy of the model. These findings support the Social Exchange Theory (Blau, 1964) and Organizational Support Theory (Eisenberger et al., 1986), asserting that fairness and organizational support foster reciprocal relationships that motivate employees to engage in voluntary, extra-role behaviors. This study contributes theoretically by extending the application of social exchange theory within the hospitality context and provides practical implications for hotel management to enhance procedural justice and organizational support as strategies to improve employees’ organizational citizenship behaviour.